High flow oxygen therapy and the work of breathing assessed by thickening fraction of the diaphragm (TFdi): just a side of the moon in cystic fibrosis patients? - Corcione, Nadia; Buonpensiero, Paolo; Esquinas, Antonio M. (Annals of Translational Medicine, 2019)
Cystic fibrosis (CF) is a life-limiting disorder affecting approximately 70,000 individuals worldwide. Over the past three decades, the median predicted survival rate of CF patients has critically improved thanks to therapies that better address serious complications of the disease (i.e., treatment of pulmonary infections, suppression of airway inflammation; management of airway secretions; interventions supporting the nutritional status) and to novel approaches that address the underlying cause of CF (i.e., drugs restoring CF transmembrane conductance regulator protein function) (1).